2017
DOI: 10.1007/s00381-017-3433-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns of children with spine and spinal cord tumors: national outcomes and review of the literature

Abstract: Hospital characteristics, length of stay, and charges remained relatively unchanged. In recent years, there has been a decreasing incidence of spine and spinal cord tumors in children. Notably, a higher mortality rate is evident over time in addition to an increase in the proportion of patients undergoing surgery. The high percentage of emergent operations suggests a weak recognition of spine tumors in children and should prompt a call for increased awareness of this cancer. In spite of these findings, lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…RT has an important role in the palliative treatment of pediatric spinal tumors 18 . A survey involving an international research consortium found that the most common indication for palliative radiation was pain management (43%), with the spine being the second most common targeted area (14%) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…RT has an important role in the palliative treatment of pediatric spinal tumors 18 . A survey involving an international research consortium found that the most common indication for palliative radiation was pain management (43%), with the spine being the second most common targeted area (14%) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Intraspinal space-occupying lesions are rare in pediatric patients and lack of uniform evidence-based management strategies [5,7]. In contrast to adult intraspinal space-occupying lesions, pediatric cases have their own characteristics in clinical manifestations, histopathology, and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The intraspinal occupying-lesions comprising tumoral and non-tumoral lesions are relatively rare in children [1][2][3][4], but can lead to serious neurological impairments if left untreated. The majority of the lesions are neoplastic lesions with the incidence less than 3 per 1000,000 persons per year, accounting for only 5% of pediatric central nervous system (CNS) tumors [5]. Notably, the most frequent pediatric intraspinal tumors are residual embryonic tissue tumors and neuroepithelial tumors.…”
Section: Introductionmentioning
confidence: 99%
“…RT has an important role in the palliative treatment of pediatric spinal tumors with pain relief in up to 83% of treated patients, with 43% able to decrease their daily dose of opioids. 12,13 Potential factors limiting the use of palliative RT in children may be the logistics involved in treatment, especially if multiple sessions are required.…”
Section: Discussionmentioning
confidence: 99%